The Kings of Algiers: How Two Jewish Families Shaped the Mediterranean World during the Napoleonic Wars and Beyond - Kalman, Julie (Princeton University Press, 2023)
"A richly detailed history of the Bacris and the Busnachs, two renowned Jewish families whose influence and reputation shook the capitals of Europe and America. At the height of the Napoleonic Wars, the Bacri brothers and their nephew, Naphtali Busnach, were perhaps the most notorious Jews in the Mediterranean. Based in the strategic port of Algiers, their interconnected families traded in raw goods and luxury items, brokered diplomatic relations with the Ottomans, and lent vital capital to warring nations. For the French, British, and Americans, who competed fiercely for access to trade and influence in the region, there was no getting around the Bacris and the Busnachs. The Kings of Algiers traces the rise and fall of these two Jewish trading families over four tumultuous decades in the nineteenth century.In this panoramic book, Julie Kalman restores their story-and Jewish history more broadly-to the histories of trade, corsairing, and high-stakes diplomacy in the Mediterranean during the Napoleonic Wars and their aftermath. Jacob Bacri dined with Napoleon himself. Thomas Jefferson, James Madison, and Horatio Nelson considered strategies to circumvent the Bacris' influence. As the families' ambitions grew, so did the perils, from imprisonment and assassination to fraud and family collapse.The Kings of Algiers brings vividly to life an age of competitive imperialism and nascent nationalism, and demonstrates how people and events on the periphery shaped perceptions and decisions in the distant metropoles of the world's great nations"--